Signs and syntax: an approach to panels reading from films to comics / Fauzi Naeim Mohamed - Mohamed, Fauzi Naeim (2009)
Both film and comics have enjoyed reputation in the public reception for being so readily accessible. While comparatively both formats have different attribute, - the film usually more temporal, the comics is more spatial- yet they share one distinctive feature that makes them so easily palatable: the elevation of the visual pleasure. This distinction can be understood and analyzed deeper by using semiotics. Semiotics is a study of sign, and sometimes seen as the science of sign system in any culture that have created, maintained and reproduced the signs. This thesis offers a semiotics analysis of comics' panels by using the platform of the semiology by Ferdinand de Saussure (one of the founding fathers of semiotics theory) and the film semiotics of Christian Metz, where in the end, I propose that the panels in comics are like shots in the film, and are structured like a language This scheme is in rhyme with all the structuralist (and post-structuralist) positions (like the critics Levi Strauss and Roland Barthes, for example) in reading culture and social convention as akin to the structural linguistic. Notably, the objective of the thesis is not only a survey on the concept of semiotics analysis but also to build a semiotics theory based from Metz's own Grand Syntagmatique. The methods of Metz's approach in reading and analyzing film shots found in Film Language: A Semiotics of the Cinema (1974) are used as the framework for the argument. By the end, I put forward a proper semiotics strategies referred as spatio-sequence (based from Metz's Grand Syntagmatique) for comics analysis. Two texts - Jeff Smith's Bone and Rejabhad's Sebuah Rumah di Tepi Sungai - are chosen as case studies to demonstrate the argument of spatio-sequence. From there weakness and strength of spatio-sequence is brought to light and reviewed. I conclude, through the case studies, that the spatio-sequence offer alternative and concise way to read the possible syntagm the panels operated and arranged in comics, which can ultimately, present new stratagem in comics theory.